Expression of Attitude by both Governor Candidates of Election Debate in Pennsylvania 2018 - Anas, Azwar; Faridi, Abdurrachman; Fitriati, Sri Wuli (English Education Journal, 2020)
This study aimed to investigate attitude in the governor election debate in Pennsylvania 2018 and to explain how application attitude in EFL Learners by both Governors candidate as reflected from the use of attitude systems are realized. Data got in the form of transcription from the video was analyzed by using Martin and White theory (2005). This study used three different marks for collecting the data, bold for effect, underline for judgement while the garlic for appreciation. Based on the finding among three types of attitude that appreciation was the dominant used compared affect and judgement. Appreciation made the speakers can be able to arrange the positive attitude than emotional in communication interpersonal and also made the speakers more appreciative one another than personal. Meanwhile, the expression of attitude resource from the two speakers took a great implication for the English learner in the classroom. From the appraising items of attitude realized by the speakers in governor election debate that students expected to use it for more pro active in teaching learning process since positive respond will be respected and linguistic interaction feel pleased and enjoyable.